Tannin-modified soybean protein concentrate for wood adhesive - Leandro Esposito; Emiliano Manuel Ciannamea; Ignacio Solaberrieta; Juan Carlos Piter; Roxana Alejandra Ruseckaite; Pablo Marcelo Stefani (Journal of Applied Research in Technology & Engineering, 2022)
Soybean protein concentrate (SPC) modified with condensed mimosa tannin (CT) were employed as eco-friendly and formaldehyde-free adhesives for glued-wood joints. Eucalyptus grandis wood boards free of knots and cracks were used as substrate. Thermogravimetric analysis (TGA) showed that tannin provided higher thermal stability to the adhesive, which allowed expanding the temperature range for hot pressing. Apparent viscosity and dynamic angle contact were measured to evaluate the influence of tannin content on rheological behaviour and the wettability process. A classic shear-thinning behaviour was observed for all adhesives. Apparent viscosity and equilibrium contact angle reached a maximum value for low CT content. This effect was attributed to the existence of associative interactions between CT and SPC. Bonding quality parameters (wood failure percentage and shear strength) of the glued-wood joints were measured according to EN 302-1:2004 standard. 1 % CT w/w on SPC adhesive showed the best performance for dry conditions. These adhesives were suitable for glued-wood joints for indoor environments.